In vitro trypanocidal activity of macela (Achyrocline satureioides) extracts against Trypanosoma evansi - Baldissera M.D. (2014)
The aim of this study was to verify the trypanocidal effectiveness of aqueous, methanolic, and ethanolic extracts of Achyrocline satureioides against Trypanosoma evansi in vitro. A. satureioides extracts, known as macela, were used on trypomastigotes at different concentrations (1, 5, 10, 50, 100, 500, and 1,000 μg/ml) and exposure times (0, 1, 3, 6, and 9 hr). A dose-dependent effect was observed when the 3 extracts were tested. The concentrations of 1, 5, and 10 μg/ml were not able to kill trypomastigotes until 3 hr after exposure, and the highest concentrations (500 and 1,000 μg/ml) were able to kill all trypomastigotes after 1 hr. When the time of exposure was increased up to 9 hr, the concentrations at 50 and 100 μg/ml were 100% effective to 3 extracts. The chemical analysis of the extracts revealed the presence of flavonoids, a trypanocidal compound already described. Based on the results, we can conclude that the A. satureioides extracts exhibit trypanocidal effects. © 2014, Korean Society for Parasitology and Tropical Medicine.